2010
DOI: 10.1021/ac101878a
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Peptide Isomers with Variant Modified Sites by High-Resolution Differential Ion Mobility Spectrometry

Abstract: Many proteins and proteolytic peptides incorporate the same post-translational modification (PTM) at different sites, creating multiple localization variants with different functions or activities that may coexist in cells. Current analytical methods based on liquid chromatography (LC) followed by tandem mass spectrometry (MS/MS) are challenged by such isomers that often co-elute in LC and/or produce non-unique fragment ions. The application of ion mobility spectrometry (IMS) was explored, but success has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
159
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(170 citation statements)
references
References 56 publications
11
159
0
Order By: Relevance
“…Previous studies have reported the benefits of FAIMS to improve proteome coverage and to reduce the extent of co-fragmentation that impedes the identification of low-abundance peptide ions (28)(29)(30)(31)(32)(33). The separation capability of FAIMS also facilitates the resolution of isomeric peptides, including histone variants and isomeric phosphopeptides (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Furthermore, the reduction of peptide co-elution and co-fragmentation observed with FAIMS can significantly improve the accuracy and the comprehensiveness of multiplex proteomic analyses (45).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the benefits of FAIMS to improve proteome coverage and to reduce the extent of co-fragmentation that impedes the identification of low-abundance peptide ions (28)(29)(30)(31)(32)(33). The separation capability of FAIMS also facilitates the resolution of isomeric peptides, including histone variants and isomeric phosphopeptides (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Furthermore, the reduction of peptide co-elution and co-fragmentation observed with FAIMS can significantly improve the accuracy and the comprehensiveness of multiplex proteomic analyses (45).…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution FAIMS appears able to generally separate the localization variants for all PTMs baseline, as demonstrated for phosphorylation 24,30) (80 Da, Fig. 4), O-linked glycosylation (by N-acetyl-galactosamine, 221 Da), 31) acetylation (42 Da), 32) and the smallest additive PTM-methylation (14 Da).…”
Section: )mentioning
confidence: 81%
“…In particular, MS/MS can tell apart only two of three or more localization isomers because all fragments of others (with either collision-induced or electron capture/transfer dissociation) are isobaric to those from a mixture of the first two. 24,27) Consequently, PTMs are often assigned to a protein region rather than a residue, 28) although variants with PTMs at nearby sites may have different and even opposite activities in vivo.…”
Section: Vol 2 (2013) S0011mentioning
confidence: 99%
See 2 more Smart Citations